Development of CATIA Machining Process Template as a Varian CAPP for Mould Machining - Nanang Ali Sutisna (President University, 2018)
Mould manufacturing is a time consuming process and a large portion of the time is used for machining process involving process planning and execution on machine. Since there are similarities in machining process for various different moulds, the process planning can be automated by applying a process template that has been proven to be the best practice for mould machining, such as the best machining parameters and sequence. The automation of process planning, so called Computer Aided Process Planning (CAPP), in this research is integrated with Computer Aided Design (CAD) and Computer Aided Manufacturing (CAM) processes using CATIA V5 software. Due to the nature of mould machining that has similarities for different moulds, the CAPP developed using Variant type, where the best machining process is stored in the database and can be used as a process template for future machining process.Keywords: CAD, CAM, CAPP, CATIA V5.